Life history of a cyprinid species in non‐regulated and regulated rivers from permanent and temporary Mediterranean basins. Issue 6 (9th November 2014) - Alexandre, C. M.; Ferreira, M. T.; Almeida, P. R.
Abstract: Streamflow variability, natural and human induced, has been suggested as a driver of life history differences among freshwater fish populations. During 1 year, we collected bimonthly and fortnightly samples from four populations of Iberian barbel, inhabiting permanent and temporary Mediterranean rivers with non‐regulated and regulated flow regimes. We analysed data for fish age, growth and reproduction to (i) compare barbels' life cycles between permanent and temporary non‐regulated rivers; (ii) assess the effect of two types of flow alteration in these traits; and (iii) identify flow variables significantly related with growth and reproductive cycles. Regional differences were related with the age of first maturation, growth rate and timing and duration of the reproductive season. Flow regulation promoted a decrease of fish growth rates, condition and gonad activity and an increase of maximum length and longevity. Seasonal variation of growth and gonad maturation were related with temperature and streamflow components. This study offers a multi‐regional perspective of the relationship between fish biological cycles and streamflow variability, providing water resource managers with needed perspective about the effect of anthropogenic alteration of streamflow magnitudes. Copyright © 2014 John Wiley & Sons, Ltd.